Eating disorders : understanding causes, controversies, and treatments - Reel, Justine J. (Greenwood, an imprint of ABC-CLIO, LLC, 2018)
This encyclopedia offers resources for readers interested in learning more about eating disorders, including reference entries, interviews, scholarly debates, and case studies. It examines eating disorders as the forms they can take; their causes and potential complications; and how they can best be treated and prevented. It also examines the influence had by cultural factors such as the fashion industry, television and movies, and social media.